The skeleton key - Softley, Iain.; Kruger, Ehren, 1972-; Bobker, Daniel; Shamberg, Michael; Sher, Stacey; Hudson, Kate, 1979-; Rowlands, Gena.; Hurt, John, 1940-; Sarsgaard, Peter; Bryant, Joy, 1976-; Mindel, Daniel; Hutshing, Joe.; et al. (Universal City, CA : Universal Pictures, 2005)
When Caroline Ellis takes a job as a hospice worker in Louisiana's bayous, she unlocks a deadly secret involving magic, conjure, and sacrifice that pulls her into a terrifying world of strange, frightening, and unexplained incidents. The key to escaping may lie in a decrepit attic, but if she dares to believe in what she discovers, everything she fears will become real.
Special features: Deleted scenes with commentary by director Iain Softley; "Behind the locked door" - Making 'The skeleton key'; exploring Voodoo/Hoodoo; recipe & ritual: making the perfect Gumbo; blues in the Bayou; Kate Hudson's ghost story; plantation life; casting 'The skeleton key'; John Hurt's story; a house called Felicity; Gena's love spell; audio commentary with director Iain Softley.
Director of photography, Dan Mindel ; editor, Joe Hutshing ; music, Ed Shearmur ; production designer, John Beard.
Kate Hudson, Gena Rowlands, John Hurt, Peter Sarsgaard, Joy Bryant, Maxine Barnett.
MPAA rating: PG-13; for violence, disturbing images, some partial nudity and thematic material.
DVD, region 1, 1.33:1 presentation ratio; Dolby Digital 5.1 surround, dual layer.
English, dubbed French or dubbed Spanish dialogue, English, French or Spanish subtitles; closed-captioned.
Keywords: Hospice nurses -- Louisiana -- Drama; Voodooism -- Louisiana -- Drama; Bayous -- Louisiana -- Drama; Feature films; Horror films; Films for the hearing impaired